Hubungan Kesejahteraan, Reward, Budaya Kerja, dan Kepemimpinan terhadap Motivasi serta Kinerja Tenaga Kependidikan Non-ASN UNNES - Riza Firmansyah; Ali Ismunadi; Yuliana Mawarti; Lisa Safitri; Arbina Peni Susanti (Institut Agama Islam Hidayatullah Batam, 2025)
This study aims to analyze the level of welfare, rewards, work culture, leadership style, motivation, and performance of non-civil servant educational staff at UNNES through a descriptive quantitative approach. The research population consisted of 157 permanent non-civil servant educational staff at UNNES, all of whom were sampled through total sampling. Data were collected using a Likert questionnaire and analyzed using descriptive statistics and Pearson's correlation in a non-inferential framework. The results show that all variables are in the high category, with the highest correlation between Motivation and Performance (r = 0.714). The descriptive regression model showed that X1–X4 explained 74.1% of the variation in Motivation (R² = 0.741), while all variables explained 71.2% of the variation in Performance (R² = 0.712). The findings emphasize the urgency of strengthening supportive leadership and work culture as the foundation for improving institutional performance.